Kepemimpinan Karismatik TGH Burhanuddin Dalam Menanamkan Budaya Religius di Pondok Pesantren Darus Shiddiqien NW Mertak Paok - Gunawan, Hendri (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2019)
The purpose of this study was to determine the charismatic leadership of TGH Burhanuddin and his strategy in shaping the Religious Culture at Darus Shiddiqien Islamic Boarding School, NW Mertak Paok. This study uses a qualitative research type using a phenomenological approach. Sources of data in this study use primary data sources and secondary data. Collecting data in this study using observation techniques, interviews, and documentation. Data analysis through data collection, data reduction, data display, and concluding. Checking the validity of the data using technical triangulation and source triangulation. The results showed: first, TGH. Burhanuddin as a charismatic leader with high authority him highly admired and highly respected by all residents of Islamic boarding schools and the surrounding community. The authority of TGH Burhanuddin emerged from the family tree which was the son of the founder of the Darus Shiddiqien Islamic Boarding School NW Mertak Paok and he was a pious, pious Tuan Guru Haji. Second; TGH Burhanudin's strategies in instilling a Religious Culture are: (1) Becoming a role model; such as discipline, and respect; (2) Habituation; greeting and greeting, respecting each other, praying together, praying in congregation, recitation every morning, hiziban and reading the Qur'an. (3) Creating a religious environment; students wear sarongs and caps every day, female students are required to wear a headscarf, and dress Islamically such as wearing skirts and robes. Third; Forms of religious culture at Darus Shiddiqien Islamic Boarding School Mertak Paok, including; (1) Religious culture in schools, such as; (a) praying together, (b) praying in the morning before entering class, (c) praying sunnah dua, (d) praying zuhur in congregation in the hall, (e) maintaining cleanliness. (2) Religious culture in the hostel, such as; (a) Smiles, greetings, and greetings, (b) obligatory fardu prayers in congregation, (c) studying the yellow book (mudzakarah), (d) weekly hiziban, (e) fasting Monday and Thursday. Keywords: Leadership, Charismatic, Religious Culture